2021
DOI: 10.1371/journal.pone.0247303
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bile acid composition in high fat diet-induced nonalcoholic fatty liver disease in obese diabetic rats

Abstract: Bile acid has attracted attention as a signal transmission molecule in energy metabolism. Although a high-fat diet (HFD) or obesity is known to increase hepatic fat content and alter bile acid composition, the changes in bile acid composition due to HFD or obesity remain to be elucidated. We sought to examine the bile acid composition in high fat diet-induced non-alcoholic fatty liver disease (NAFLD) in obese diabetic rats. Eight-week-old male spontaneously diabetic Torii fatty (SDTF) rats or control rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…Consequently, CA administration increased the ratio of mainly gram-positive Firmicutes to gram-negative Bacteroidetes [ 204 ]. A similar impact on microbiota has been observed as a consequence of HFD-feeding, which is known for triggering increased BA levels [ 205 , 206 ] and is also the case for obesity [ 207 , 208 ]. Importantly, bacteria can be trained and adapt to the presence of BAs [ 199 , 209 , 210 , 211 ], but conditioning the microbiome by applying HFD can amplify host energy harvest and inflammation [ 208 , 212 , 213 ].…”
Section: Basmentioning
confidence: 55%
“…Consequently, CA administration increased the ratio of mainly gram-positive Firmicutes to gram-negative Bacteroidetes [ 204 ]. A similar impact on microbiota has been observed as a consequence of HFD-feeding, which is known for triggering increased BA levels [ 205 , 206 ] and is also the case for obesity [ 207 , 208 ]. Importantly, bacteria can be trained and adapt to the presence of BAs [ 199 , 209 , 210 , 211 ], but conditioning the microbiome by applying HFD can amplify host energy harvest and inflammation [ 208 , 212 , 213 ].…”
Section: Basmentioning
confidence: 55%
“…Bile acid circulation is altered in obesity [68][69][70]. Recent experiments investigated the role of NT in mediating the association between HFD-induced decreases in plasma bile acid levels and the presence of obesity, using whole body knockout mice for the NT gene [71].…”
Section: Nt and Bile Acid Metabolismmentioning
confidence: 99%
“…Indeed, substantial evidence has already demonstrated that an elevation in circulating bile acids levels seems to indicate improved energy homeostasis. For example, decreased circulating bile acids were observed in HFD-fed SD rats [ 58 ]. Particularly, HFD feeding was also found to lower circulating levels of CA, DCA [ 58 ], ω-muricholic acid (MCA), and α-MCA [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased circulating bile acids were observed in HFD-fed SD rats [ 58 ]. Particularly, HFD feeding was also found to lower circulating levels of CA, DCA [ 58 ], ω-muricholic acid (MCA), and α-MCA [ 59 ]. In contrast, this HFD-induced decrease in plasma bile acids could be improved in neurotensin-deficient mice [ 60 ].…”
Section: Discussionmentioning
confidence: 99%